Testing the optical methods by using the multi-level holographic grating - Barchuk, О.I.; Braginets, Y.V.; Klimov, O.S.; Oberemok, Y.A.; Savenkov, S.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
In this work the interaction peculiarities of electro-magnetic optical range
radiation with gratings’ surfaces are investigated. The multilevel diffractive holographic
grating is proposed to be used for the polarization optical methods testing. This object
allowed to obtain simultaneous visualization of different spatial frequencies and to
estimate both structure and surface peculiarities when working with 3D-objects. Using
this additional information one can remove uncertainty in solution of the inverse problem
of ellipsometry related with ellipsometric angles periodicity. Thereby, multiangle
ellipsometry allowing investigation of the specular reflection component could be used to
study submicron peculiarities of the object. We have also presented the basic aspects of
ellipsometric method optimization. It was shown that anisotropy parameters, such as
linear amplitude anisotropy and linear phase anisotropy, obtained from ellipsometric
measurements are the most effective to ascertain the submicron characteristic dimension
of material.